PKM Peningkatan Wawasan Industri Mahasiswa Melalui Kemahiran Bahasa Jerman - Lapasau, Merry; Arliyanto, P Yudi Dwi; Debora, Fransisca; Raras, Marta Hayu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
This community service (hereinafter, PkM) is the result of a collaboration between University Indraprasta PGRI Jakarta and Politeknik Meta Industri Cikarang which aims to increase the industrial insight of students and general participants through proficiency in German. This activity was held on December 17, 2020 through a media zoom meeting with a power point and smartboard interactive whiteboard (hereinafter, IWB) presentation for two hours, which was attended by around 100 participants. The material is divided into three parts, namely 1) Introduction to the industrial world in Germany, 2) German Industry in Indonesia, and 3) Introduction to German language and culture. At the end of the activity, participants write down suggestions and comments. In general, it can be concluded that this PkM activity increases the participants' insight and understanding of industry in Germany and German language which is useful for industrial engineering students and society in general.